Penerapan Problem Based Instruction dalam Meningkatkan Hasil Belajar Siswa pada Konsep Thaharah - Lessy, Ramla; Suruali, Husni (Lembaga Intelektual Muda (LIM) Maluku, 2021)
This study aims to determine the application of Problem Based Instruction in improving student learning outcomes on the concept of thaharah. The type of research used is Classroom Action Research which consists of four stages, namely planning, implementation, observation, and reflection with a total of 32 subjects. Data collection techniques are by conducting tests and observations, and documentation. Observation is carried out by an observer to observe the learning activities of teachers and students and the test is used to find out the learning outcomes of students after participating in learning activities using problem-based learning. The results of data analysis on learning outcomes, it was obtained that learning using problem-based learning can improve student learning outcomes. This is shown by the increase in the average score of students, namely in the initial test of 52.29 with a percentage of completion of 21.875%, increasing in the first cycle to 66.04 with a percentage of completion of 68.75%. Meanwhile, in the results of the second cycle test, the average score was 80.21 with a percentage of completion of 96.875%.